2021
DOI: 10.3390/agronomy11112355
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Bioinoculants Based on Mycorrhizal and Trichoderma spp. Fungi in an Apple Tree Nursery under Replantation Conditions

Abstract: Both mycorrhizal and Trichoderma spp. fungi are known for antagonistic effects against certain biological pathogens causing apple replant disease (ARD). The aim of this study was to assess the effectiveness of the bioinoculants based on endomycorrhizal and Trichoderma spp. fungi on the biological properties of soil as well as the parameters of the apple tree growths in a fruit tree nursery under replantation conditions. A two-year experiment was conducted on Jonagold apple trees grafted on to M.9 rootstock in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…Trichoderma spp. was reported to improve the activity of dehydrogenase and positively amend the soil properties [ 83 ]. Dehydrogenase is one of the most important soil enzymes, which is an indicator of soil quality due to different stress, or management practices.…”
Section: Discussionmentioning
confidence: 99%
“…Trichoderma spp. was reported to improve the activity of dehydrogenase and positively amend the soil properties [ 83 ]. Dehydrogenase is one of the most important soil enzymes, which is an indicator of soil quality due to different stress, or management practices.…”
Section: Discussionmentioning
confidence: 99%
“…Their application had no significant effect on plant growth, and sometimes even worse results than in the control were obtained. Zydlik et al [35] also found a similar height in maiden apple trees of the 'Jonagold' cultivar on the M.9 rootstock after the application of the Th fungus in replanted soil compared to the control. A significantly better height in maiden apple trees of the 'Topaz' cultivar on the M.26 rootstock was obtained by Grzyb et al [36], which was 127 cm.…”
Section: Maiden Apple Tree Growth After Applying the Fungimentioning
confidence: 78%
“…on pea roots in vitro mycoparasitic activity against AMF Rousseau et al 1996 T. harzianum and Glomus versiforme powdery mildew ( Erysiphe flexuosa ) in cowpea greenhouse enhancement of cowpea seedlings’ resistance to powdery mildew and growth promotion (increase in shooth dry weight) Omomowo et al 2018 T. harzianum and AMF Fusarium wilt in bananas greenhouse reduction of Fusarium wilt infection, increase in plant height, pseudostem diameter and root weight Castillo et al 2019 T. asperellum and Beauveria bassiana Asian corn borer on maize in vitro and greenhouse suppression of the Asian corn borer’s immune response resulting in 98.3% mortality, induction of plant resistance Batool et al 2020 Trichoderma spp. and mycorrhizal fungi apple replant disease tree nursery induction of growth in root system and aerial parts of trees in replant soil Zydlik et al 2021 T. viride and dark septate endophytes drought stress of Astragalus mongholicus growth chamber synergism in driving the rhizosphere microbiome and plant adaptive responses towards drought resistance, increase in plant biomass, plant height and root surface area He et al 2022 Trichoderma with bacteria T. harzianum , B. subtilis biocontrol of the anise pathogen Puccinia pimpinellae field moderate decrease in disease incidence and severity in treatments due to pathogen inhibition by chitinase production Saber et al 2009 Trichoderma sp., T. atroviride , T. virens , P. chlororap...…”
Section: Multicomponent Inoculants Containing Trichodermamentioning
confidence: 99%